Desmoid tumor presenting 2 years after elective Roux-en-Y gastric bypass: a case report and review of the literature. Issue 2 (7th February 2020) - Sierra-Davidson, Kailan; Anderson, Geoffrey; Tanabe, Kenneth; Meireles, Ozanan R
Abstract: Desmoid tumors are rare malignancies derived from myofibroblasts, which can cause significant morbidity due to life-threatening invasion of local structures. Risk factors include familial adenomatous polyposis, antecedent surgical trauma and estrogen exposure. We described a previously healthy 27-year-old female in whom a desmoid tumor developed 2 years after a Roux-en-Y gastric bypass was performed for the treatment of obesity. Computed tomography scan demonstrated a 16-cm complex density intra-abdominal mass. Exploratory laparotomy was performed, revealing a mass firmly adherent to the Roux limb, as well as the jejunojejunostomy and distal portion of the bilopancreatic limb. En bloc resection of the mass and the Roux limb was required, as well as reconstruction of the Roux-en-Y anatomy. This case describes a unique, long-term complication of bariatric surgery, in light of a growing population of patients with altered gastric anatomy.